Innovations in Environmental Remediation: Use of Suillus Luteus in the Removal of Heavy Metals from Acid Mine Drainage - Licapa-Redolfo, Gladys S.; Aguilar Reyna, Jhon; Oblitas Jauregui, Cristofer; Cáceres Perez, Shonel (LACCEI, 2024)
In the current investigation, the objective was to determine the level of efficiency of the fungus "suillus luteus" in the removal of As, Cd, B and Li in acid mine drainage from a mining environmental liability located in Hualgayoc. The means applied in the remediation have the Regional Water Laboratory and the UPN, turning the "suillus luteus" fungus into an economical and effective alternative. To begin the mine drainage, it is typified through a total metal analysis of the sample point (PM) prior to treatment, reaching initial concentrations for the PM of 0.168 mg/L of As; 0.230 mg/L of Cd; 0.503 mg/L of B and 0.119 mg/L of Li, obtaining a pH of 2.42. Applying the experimental design for the treatment of mine drainage, doses of 10, 20 and 30g of biomass of the fungus and contact times of 1, 2 and 3h were added, attributing the nine treatments to the mine drainage sample according to the test, achieving optimal remediation results through a dosage of 30g of fungus and 3h of contact time. After the treatment with biomass of the fungus, it was possible to remove As in 30.36% with 20g and 1 h, Cd in 61.21% with 30g and 3h, B in 87.07% with 20g and 3h and Li in 90.76% with 10g and 1h and increase the pH until reaching a value of 5.36, deriving it as a complementary and optional treatment to deal with environmental conflicts due to acid effluents.